Challenges in Implementing Sharia-Based Education: Balancing Regional Autonomy and Children’s Rights in Aceh - Mukhlis Mukhlis; Muhammad Iqbal; Maya Safitri; Hasniyati Hasniyati (Khazanah Hukum, 2025)
This study analyzes the implementation of Sharia-based education in Aceh through the perspective of regional autonomy and children's rights.  This multidisciplinary study reveals the tension between Aceh's education policies (Law No.  11/2006 and Qanun Education) with the obligation of children's rights (children's rights convention Articles 28-29 and Child Protection Law No.  35/2014). Findings show that some schools do not meet inclusive standards, religious materials are less multicultural, and only some teachers are trained in inclusive pedagogy with infrastructure gaps.    The impact on children's rights is significant: female dropout rates are higher due to child marriage and only some schools are disability friendly.   Policy analysis revealed that Qanun has not fully adopted the principle of inclusivity, while policies in the district still ignore marginalized groups.  The research introduced the "Balanced Integration" model, which was piloted in 10 schools, successfully improving the indicators of inclusivity by aligning Islamic values with the principles of the children's rights convention article 29.  Other findings show that hybrid programs (tahfiz-STEM) increase student acceptance in universities. Policy implications include: (1) harmonization of Qanun with human rights standards, (2) children's rights-based teacher training, and (3) policy impact monitoring system.  The study offers an operational framework linking regional autonomy, Islamic identity, and children's rights, with specific recommendations to ensure Sharia education in Aceh meets three pillars: local wisdom, religious values, and universal human rights standards. The findings contribute to the global discourse on multicultural education in Muslim societies suggesting that educational autonomy can be implemented without sacrificing children's basic rights.